2022
DOI: 10.1007/s00210-022-02243-1
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction

Abstract: Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 55 publications
(62 reference statements)
2
28
0
Order By: Relevance
“…So further indepth study is needed. Notably, a recent study reported that Cana exert its cardiovascular benefits partly via its mitigation of ferroptosis in a rodent model of HFpEF (15), which provide a new idea for the research of SGLT2is in heart disease, even DCM. So far, the cardioprotective mechanisms of Cana on DCM are not fully clear and needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So further indepth study is needed. Notably, a recent study reported that Cana exert its cardiovascular benefits partly via its mitigation of ferroptosis in a rodent model of HFpEF (15), which provide a new idea for the research of SGLT2is in heart disease, even DCM. So far, the cardioprotective mechanisms of Cana on DCM are not fully clear and needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…(3) DCM + Cana group: DCM model mice were treated with 20 mg/kg/d canagliflozin (15,19,20) (C126191, Aladdin, China) for 6 weeks. On the last day, electrocardiogram examination was performed after the drug intervention, then all animals were weighted and sacrificed, heart tissues were removed freshly and aseptically for measurements.…”
Section: Methods Animals' Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major milestone in the treatment of HFpEF, and so SGLT2i is of significant interest. Canagliflozin was shown to block ferroptosis and treat HFpEF [ 77 ], which demonstrated that the intervention of ferroptosis could be used as a new attempt. Further research is needed to clarify the causal relationship and specific mechanism between ferroptosis and HFpEF and provide an opportunity for designing new therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of GPX4 and ferritin (Fth1) was significantly downregulated in a pressure overload-induced heart failure model in rats, while knockdown of TLR4 or NOX4 gene restored the expression of GPX4 and Fth1 in cardiomyocytes and improved ventricular remodeling and LV function in rats with heart failure [ 76 ]. It is worth noting that Sai Ma et al [ 77 ] demonstrated that ferroptosis might be a key mechanism in a rat model of HFpEF with proteomics, which was blocked following treatment with canagliflozin, a sodium–glucose cotransporter 2 inhibitor (SGLT2i).…”
Section: Research Progress Of Anti-ferroptosis In Hfpefmentioning
confidence: 99%